(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
The development of grouper’s cultivation in Kepulauan Seribu is growing rapidly but there were numerous problems with its cultivation such as limited suitable locations, negative environmental impacts, and land-use conflicts. Lack of information regarding the characteristics of water that suitable for aquaculture will lead to improper use of the location. To prevent this problem, this study aimed to identify and determine suitable locations for grouper’s cultivation in Kepulauan Seribu by using the Fuzzy AHP multi-criteria evaluation model based on geographic information systems. The weighting parameter results showed that the distance to the resident is 37.28%, the water current is 26%, the distance to the market is 17.21%, the distance to the road is 11.33%, the distance to the pier is 5.34%, and water depth is 2.84% with a consistency ratio of 0.0337. The waters of Tidung island, Panggang island, Pramuka island, Karya island, Kelapa island, Kelapadua island, Kaliage island, and Pari island are ideal waters for grouper aquaculture activities because they have suitable water conditions and social infrastructure factors. The use of a multi-criteria evaluation model with Fuzzy AHP based on geographic information systems provided relevant analytical results in assigning a weighted score and determining the most dominant criteria that build around the importance of each parameter to other parameters in influencing the cultivation suitability class.